Substitute running outputs in elite youth male soccer players: less peak but greater relative running outputs - G. Sydney, Michael; Ball, Nick; K. Mara, Jocelyn; Chapman, Dale; Wollin, Martin (Biology of Sport, 2023)
Coaches consider substitute players to be a substantial factor in influencing the outcome of a soccer match. Substitute players are expected to make physical impact on the match by superseding the running output of the player they replaced and are a key tool for managing in-game fatigue and influencing the outcome of a game. This study investigated the physical impact and internal response of substitute players, compared to starting and full-match players. We also sought to determine if differences between substitution statuses were influenced by playing position. Players wore 15-Hz global positioning system tracking devices across 29 competition matches and were categorised according to their substitution status (full-match, starters, substitutes) and playing position (external defender, midfield, external attacker and central attacker). Peak total (TD) and high-speed running (> 5.0 m/s) distance (HSRD) were calculated using 1-, 2- and 5-minute rolling epochs. Relative running demands were reported as TD and HSRD per minute of total playing time. Substitute players performed less peak TD and HSRD in 1-, 2- and 5-minute epochs, and reported lower RPE compared to starting and full-match players. In contrast, substitutes performed greater relative HSRD per minute than starting and full-match players (p < 0.001, |d| range = 0.35–1.34). In conclusion, substitute players may have a relative physical impact but do not replicate or supersede the peak demands of full-match players. Coaches and practitioners should implement targeted warm-up interventions to enhance substitute readiness to meet the peak running demands in order to have a more effective physical impact.